2023
DOI: 10.1038/s41396-023-01357-5
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobial migration toward roots mediated by FadL-ExoFQP modulation of extracellular long-chain AHLs

Abstract: Migration from rhizosphere to rhizoplane is a key selecting process in root microbiome assembly, but not fully understood. Rhizobiales members are overrepresented in the core root microbiome of terrestrial plants, and here we report a genome-wide transposon-sequencing of rhizoplane fitness genes of beneficial Sinorhizobium fredii on wild soybean, cultivated soybean, rice, and maize. There were few genes involved in broad-host-range rhizoplane colonization. The fadL mutant lacking a fatty acid transporter exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Moreover, the impact of the rhizosphere soil was discovered to be more significant on fungi than bacteria. Notably, a higher number of OTUs linked to Burkholderiales and Rhizobiales are found in the rhizosphere soil, which constitutes the core root microbiome of terrestrial plants (Ji et al, 2023 ). Rhizobiales have been identified as endophytes in different plants and have been shown to contribute to the growth of crops such as rice and wheat (Yanni et al, 2016 ; Wu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the impact of the rhizosphere soil was discovered to be more significant on fungi than bacteria. Notably, a higher number of OTUs linked to Burkholderiales and Rhizobiales are found in the rhizosphere soil, which constitutes the core root microbiome of terrestrial plants (Ji et al, 2023 ). Rhizobiales have been identified as endophytes in different plants and have been shown to contribute to the growth of crops such as rice and wheat (Yanni et al, 2016 ; Wu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the bacterial side, using classical genetics or large-scale transposon insertion mutant libraries, several studies have shown that hundreds of genes are involved in the competitive ability of rhizobia to form nodules ( Pobigaylo et al., 2008 ; Wheatley et al., 2020 ; Mendoza-Suárez et al., 2021 ). Beyond NF biosynthesis and regulatory genes, genes involved in motility and chemotaxis, or other functions that help bacteria to migrate near the roots ( Caetano-Anollés et al., 1988 ; Wheatley et al., 2020 ; Ji et al., 2023 ), and in surface polysaccharide biosynthesis ( Pobigaylo et al., 2008 ; Janczarek et al., 2009 ) were shown to be important for competitive nodule formation. Also, the bacterial capacity to metabolise components found in root exudates such as the homoserine or mimosine ( Soedarjo and Borthakur, 1998 ; Vanderlinde et al., 2014 ), particular sugars such as erythritol ( Yost et al., 2006 ; Wheatley et al., 2020 ), rhamnose ( Oresnik et al., 1998 ), myo-inositol ( Fry et al., 2001 ) or amino acids such as proline ( Jimenez-Zurdo, 1995 ) contribute to nodulation competitiveness.…”
Section: Microbial Interactions Interfering With the Initiation Of No...mentioning
confidence: 99%
“…In this approach, genes conferring a fitness advantage under the given condition are identified by their absence of Tn insertions compared to the standard growth condition, while those causing a disadvantage exhibit a greater number of insertions [44][45][46] . Tnseq has been used to identify essential genes (also referred to as core genes), for growth in standard laboratory conditions, genes important after exposure to environmental stressors, and also to better understand the molecular basis of bacteria host interactions 47 , including the alpha-rhizobia-legume symbiosis [48][49][50][51][52] . An example is the Bradyrhizobium diazoefficiens USDA 110 T spc4 (previously B. japonicum USDA110) Tn-seq library, which was used to identify putative essential genes during aerobic growth in yeast extract-arabinose-gluconate medium 48 .…”
Section: Main Text Introductionmentioning
confidence: 99%